2011
DOI: 10.1111/j.1748-0361.2011.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Readiness Between Rural Hospitals and Primary Care Providers for Telemedicine Adoption and Implementation: Findings From a Statewide Telemedicine Survey

Abstract: Telemedicine continues to be a viable solution for bridging geographic access gaps to a variety of specialty care. Users need assistance in understanding legal implications, care coordination, billing for services, and disaster data recovery. In rural areas, hospitals appear to best embody characteristics of facilities that successfully implement telemedicine and have the greatest degree of readiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
(36 reference statements)
3
29
0
Order By: Relevance
“…The use of this approach may be especially important for research focused on issues in small organizations with their inherent sample size limitations and variable and changing structural and communication characteristics. Our study findings support important aspects of the conceptual model of adoption of innovations, yet support the call for intensive work on instrument development for this area of inquiry [32] and need for intensive multi-variate and time analyses [17,32]. …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The use of this approach may be especially important for research focused on issues in small organizations with their inherent sample size limitations and variable and changing structural and communication characteristics. Our study findings support important aspects of the conceptual model of adoption of innovations, yet support the call for intensive work on instrument development for this area of inquiry [32] and need for intensive multi-variate and time analyses [17,32]. …”
Section: Discussionsupporting
confidence: 76%
“…All investigators championed the need for theory testing and validated measures. Published reviews indicate that to date instruments for measuring organizational readiness for change demonstrate variable operational definitions and little evidence of reliability or validity [17,32,40]. Conceptually, many of the domains and factors discussed in various models are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast and easy accessibility is an issue for patients requiring regular follow-ups and long-term monitoring, such as heart disease and diabetes patients (2). It has been reported that telemedicine can improve cost effectiveness in many cases (3;4).…”
mentioning
confidence: 99%
“…[2][3][4] In addition, the degree to which telehealth technologies have been adopted and the factors that influence whether or not institutions adopt them are not well understood. [5][6][7][8] A hospital's decision about whether to invest in telehealth is likely shaped by a range of factors. These include specific features of the hospital, such as its teaching mission, its affiliations with other institutions, and its technological capabilities.…”
mentioning
confidence: 99%